Biological properties of Serratia liquefaciens 1/2024, isolated from chicken: - VYGOVSKA Liliіa; USHKALOV, Artem; ZELENA, Liubov; USHKALOV, Valerii; SÎRBU, Cristina; VISHOVAN, Yurii (One Health & Risk Management, 2025)
Introduction. According to a study by the European Centre for Disease Prevention and Control (ECDC) for 2022-2023, Serratia spp. caused 54,406 cases of disease in 28 countries worldwide. Serratia liquefaciens is considered the second most frequently isolated organism from human clinical samples after Serratia marcescens. The aim of this study was to investigate the biological properties of S. liquefaciens isolated from chickens. Materials and methods. The study investigated a Serratia liquefaciens strain isolated in 2024 from chickens kept in a vivarium with clinical manifestations of gastrointestinal tract disorders. The aim of the study was to examine the strain S. liquefaciens. When studying the biological properties of the isolate, morphological characteristics, growth typicality, biochemical properties, pathogenicity for laboratory animals, and antibiotic sensitivity were taken into account. Results. The isolated microorganism formed colonies typical of the Serratin genus, and the cells were motile at 37°C. The enzymatic profile matched the known characteristics of S. liquefaciens. The strain produced a denser biofilm at 23°C, exhibited pathogenicity in white mice, and showed resistance to several classes of antimicrobial agents. Based on the sequencing of a 16S rRNA gene fragment, the strain was deposited in the NCBI GenBank database under accession number PQ308601.1. Conclusions. The results obtained suggest that the S. liquefaciens 1/2024 may be used as a reference strain for the differential diagnosis of enterobacteria, assessment of antimicrobial activity, and application as a laboratory control strain in experimental studies.